Scope of State Responsibility Against Terrorism in International Law Perspective; Indonesian Cases - Dian Purwaningrum Soemitro; Indra Wahyu Pratama (Jurnal Cita Hukum, 2015)
Abstract: Scope of State Responsibility Against Terrorism in International Law Perspective; Indonesian Cases. The emergence of global terrorism cases within more than a decade, marked by the tragedy of 9/11, making the issue of it being a big problem. The State as one of the subjects of International Law, into the spotlight. One of the problems that developed was the extent of the responsibility of the State towards acts of terrorism that occurred in the region of his sovereignty, which caused casualties both its own citizens or foreign nationals. In the case of terrorism that happened in Indonesia, the State's responsibility to the International Conventions implementation are very insufficient and the efforts from the country by creating a system of criminal justice to the criminal offence of terrorism has not been a maximum. There should be an obligation of the internationally imposed on it. The problem is if the terrorism was occurred will be submitted to the International Law are likely to be open to foreigners intervention. This is of course contrary to the principles of International Law. However, in the development of International Law as it has evolved in the Principle of the Responsibility to Protect and that should be accepted by any countries in order to attract the embodiment of the country against the security and Human Rights Abstrak: Lingkup Pertanggungjawaban Negara Terhadap Terorisme dalam Perspektif Hukum Internasional pada Kasus Indonesia. Munculnya kasus terorisme global dalam satu dekade, ditandai dengan tragedi 9/11 yang menjadi masalah besar. Salah satu masalah yang berkembang adalah sejauh mana tanggung jawab negara terhadap aksi terorisme yang terjadi di wilayah kedaulatannya, yang menyebabkan timbulnya korban, baik warga negaranya sendiri atau warga negara asing. Dalam kasus terorisme yang terjadi di Indonesia, pertanggungjawaban negara terlihat dalam pelaksanaan Konvensi Internasional dan upaya menciptakan sistem peradilan pidana bagi pelaku tindak pidana terorisme. Jika permasalahan terorisme diserahkan kepada Hukum Internasional, maka cenderung akan membuka intervensi asing. Hal ini tentu saja bertentangan dengan prinsip-prinsip Hukum Internasional. Namun, dalam perkembangan Hukum Internasional telah berevolusi dalam Prinsip Tanggung Jawab untuk melindungi, selain adanya keharusan setiap negara untuk menjaga keamanan dan Hak Asasi Manusia  DOI: 10.15408/jch.v2i1.1841